War and Genocide in South Sudan - Pinaud, Clémence (Cornell University Press, 2021)
War and Genocide in South Sudan traces the rise of a predatory state during civil war in southern Sudan and its transformation into a violent Dinka ethnocracy after the region's formal independence. That new state, Pinaud argues, waged genocide against non-Dinka civilians in 2013-2017.